2015
DOI: 10.1016/j.pharep.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Subacute poisoning of mice with deltamethrin produces memory impairment, reduced locomotor activity, liver damage and changes in blood morphology in the mechanism of oxidative stress

Abstract: The results obtained indicate that liver and bone marrow, apart from the central nervous system (CNS) are damaged in the course of subacute poisoning with DEL. The possible common mechanism of the damage is oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…It is known that pyrethroids can target neurons and influence physical activities in arthropods as well as mammals (Baatrup et al, 1993; Crofton et al, 1988; Frank et al, 2000; Nieradko-Iwanicka et al, 2015). It was previously shown that daily intraperitoneal injection of deltamethrin, at doses higher than we used in the current report (8.3–41.5 mg/kg body weights for 1–28 days), significantly decreased locomotive activity in female mice (Nieradko-Iwanicka et al, 2015). Because of its lipophilic nature, permethrin was found to accumulate in the nervous system at 1.5~7.5 times higher levels than in plasma after oral administration (Anadon et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that pyrethroids can target neurons and influence physical activities in arthropods as well as mammals (Baatrup et al, 1993; Crofton et al, 1988; Frank et al, 2000; Nieradko-Iwanicka et al, 2015). It was previously shown that daily intraperitoneal injection of deltamethrin, at doses higher than we used in the current report (8.3–41.5 mg/kg body weights for 1–28 days), significantly decreased locomotive activity in female mice (Nieradko-Iwanicka et al, 2015). Because of its lipophilic nature, permethrin was found to accumulate in the nervous system at 1.5~7.5 times higher levels than in plasma after oral administration (Anadon et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study states the "possible mechanism" of the damage by DLM at liver and bone marrow is oxidative stress. [37] This study shows that insecticide toxicity causes oxidative stress and oxidant or free radicals have a major role so plasma MDA and GSH level measurements can be used for insecticide toxicity evaluation. Although plasma MDA and GSH level measurements are not specific to a particular disease or toxicity, they can be used for monitorization of DLM toxicity rather than diagnosis.…”
Section: Discussionmentioning
confidence: 89%
“…The rampant use of mosquito repellants are of a serious concern for health and the environment, and their easy availability and widespread use are responsible for frequent poisoning . It has been reported that exposure to pesticides is associated with increased risk of degenerative as well as various other pathological disorders . Oxidative stress plays a crucial role in the development of several diseases such as atherosclerosis, cancer, diabetics, rheumatoid arthritis, myocardial infarction, autoimmune disease, and aging .…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been reported that exposure to pesticides is associated with increased risk of degenerative as well as various other pathological disorders. 22,23 Oxidative stress plays a crucial role in the development of several diseases such as atherosclerosis, cancer, diabetics, rheumatoid arthritis, myocardial infarction, autoimmune disease, and aging. 24,25 Administration of insecticides in acute or sub-acute doses in experimental animals has been shown to result in deviation from normal structure and function of the lung, liver, and kidney mainly due to oxidative stress 26,27 .…”
Section: Discussionmentioning
confidence: 99%